2020
DOI: 10.5210/fm.v25i11.10881
|View full text |Cite
|
Sign up to set email alerts
|

Social discourse and reopening after COVID-19

Abstract: Although the COVID-19 pandemic has not been quenched yet, many countries lifted nationwide lockdowns to restart their economies, with citizens discussing the facets of reopening over social media. Investigating these online messages can open a window into people’s minds, unveiling their overall perceptions, their fears and hopes about the reopening. This window is opened and explored here for Italy, the first European country to adopt and release lockdown, by extracting key ideas and emotions over time from 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…Feelings of fear and reduced sense of agency might be the source of similar results found on previous studies using semantic and emotional network analysis on social discourse in Italian tweets at the end of the first lockdown ( Stella, Restocchi & De Deyne, 2020 ; Stella, 2020 ). Stella (2020) showed that Italian participants tended to re-share a greater number of messages expressing fearful ideas, probably triggered by the strong affinity of the tweets’ content and the feeling of individuals following the sudden raises in the COVID-19 contagion curve after the reopening. Fear is also the emotional concept most frequently produced by Italian participants in relation to the COVID-19 concept in a word association task ( i.e., participants listed concepts coming in mind in response to a given concept) ( Mazzuca et al, 2021 ).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Feelings of fear and reduced sense of agency might be the source of similar results found on previous studies using semantic and emotional network analysis on social discourse in Italian tweets at the end of the first lockdown ( Stella, Restocchi & De Deyne, 2020 ; Stella, 2020 ). Stella (2020) showed that Italian participants tended to re-share a greater number of messages expressing fearful ideas, probably triggered by the strong affinity of the tweets’ content and the feeling of individuals following the sudden raises in the COVID-19 contagion curve after the reopening. Fear is also the emotional concept most frequently produced by Italian participants in relation to the COVID-19 concept in a word association task ( i.e., participants listed concepts coming in mind in response to a given concept) ( Mazzuca et al, 2021 ).…”
Section: Discussionsupporting
confidence: 84%
“…The results concerning the valence and dominance dimensions are consistent with the expected individuals' stronger feelings of fear and reduced sense of agency (and a consequent subjective perception of being in an out-of-control situation) in the current context, that is, an imminent threat to the humanity health (Stevenson, Mikel & James , 2007;Warriner, Kuperman & Brysbaert, 2013). Feelings of fear and reduced sense of agency might be the source of similar results found on previous studies using semantic and emotional network analysis on social discourse in Italian tweets at the end of the first lockdown (Stella, Restocchi & De Deyne, 2020;Stella, 2020). Stella (2020) showed that Italian participants tended to re-share a greater number of messages expressing fearful ideas, probably triggered by the strong affinity of the tweets' content and the feeling of individuals following the sudden raises in the COVID-19 contagion curve after the reopening.…”
Section: Panassupporting
confidence: 90%
“…Boccaletti et al, 2014) can account for multiple types of links within one network representation. Besides TFMNs (Stella, , 2020b, as described above, other cognitive approaches with multilayer networks were recently introduced in the literature. Conceptual distance in multilayer networks (combining phonological, categorical, and semantic associations) was found to be predictive of both normative word acquisition in children (Stella et al, 2017) and picture naming failures in people with a spectrum of aphasic disorders .…”
Section: Cognitive Network Open the Way To Sociocognitive Investigati...mentioning
confidence: 99%
“…Stella (2020b) built on previous results of semantic relatedness/closeness being captured by semantic network distance(Kenett et al 2017) in order to model semantic prominence in terms of closeness centrality, i.e. the mean network distance of one node to all its connected neighbours.…”
mentioning
confidence: 99%
See 1 more Smart Citation